Growth Measures and Stock Returns - Arora, Lalit; Kumar, Shailendra; Verma, Piyush (Indian Journal of Finance, 2016)
This study examined the aptness of important growth measures in the form of sustainable growth, asset growth, and sales growth in explaining stock returns of firms in the Indian manufacturing sector. Using panel data regression analysis, results provided evidence that sustainable growth rate; a forward looking approach for assessing firm’s performance, emerges as a significant variable in explaining the stock returns. Results remain unchanged even after introducing the established determinants of stock returns such as BE/ME and firm size in the regression equations. Asset growth emerged as an important channel through which sustainable growth can be linked with stock returns.